Transparent anti-impact modifier for yellowing-resistant polyvinyl chloride and preparation method of transparent anti-impact modifier
By adopting a graft copolymer with a hard-core-soft-core-hard shell three-layer structure as a transparent impact modifier for polyvinyl chloride, the problem that impact modifiers in the prior art cannot take into account both yellowing resistance, achieving better impact resistance and fluidity, and reducing yellowing phenomenon.
Patent Information
- Application Number
- CN202510377270.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-28
AI Technical Summary
The transparent impact modifier added to existing polyvinyl chloride transparent products cannot take into account both yellowing resistance, resulting in the impact of performance and appearance.
The graft copolymer composed of a hard core layer, a soft core layer and a hard shell layer is used as the transparent impact modifier for polyvinyl chloride. The hard core layer is mainly prepared from styrene, α-methylstyrene and water. The soft core layer is mainly prepared from alkyl acrylate and water. The hard shell layer is a methacrylate polymer.
It has achieved good impact resistance while taking into account yellowing resistance, reducing the oligomer generated by incomplete depolymerization of methyl methacrylate, reducing the yellowing phenomenon, and improving the fluidity of the modifier in polyvinyl chloride and the impact resistance of the products.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of impact modifiers for polyvinyl chloride, and in particular to a yellowing-resistant transparent impact modifier for polyvinyl chloride and a preparation method thereof. Background Art
[0002] Polyvinyl chloride material is the third largest synthetic polymer plastic in the world, with a wide range of applications and a very large demand. Polyvinyl chloride material itself has good chemical stability, corrosion resistance, high hardness, high strength, fire resistance and flame retardancy (self-extinguishing), reliable insulation performance, smooth surface, no water absorption, no deformation, easy processing and other advantages, plus polyvinyl chloride plastic itself has a certain degree of transparency, the advantages of polyvinyl chloride transparent products are very obvious, it is an excellent thermoforming material. Polyvinyl chloride material can replace part of stainless steel and other corrosion-resistant synthetic materials, and is widely used in chemical, petroleum, electroplating, water purification equipment, environmental protection equipment, mining, medicine, electronics, communications and decoration industries.
[0003] However, polyvinyl chloride products are hard and brittle materials with poor impact resistance. Impact modifiers need to be added during the molding process. Generally, styrene is added to the transparent impact modifier to balance the refractive index and improve transparency, but it also leads to poor high temperature resistance and yellowing resistance. Therefore, it is difficult to balance the transparency, impact resistance and yellowing resistance of current polyvinyl chloride products, which can easily affect the final performance and appearance of transparent polyvinyl chloride products. Summary of the invention
[0004] In order to solve the problem that the transparent impact modifier added to the above-mentioned transparent polyvinyl chloride products cannot take into account the yellowing resistance, the present invention provides a transparent impact modifier for polyvinyl chloride and a preparation method thereof.
[0005] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a transparent impact modifier for polyvinyl chloride that is resistant to yellowing, wherein the transparent impact modifier for polyvinyl chloride is a graft copolymer consisting of a hard core layer, a soft core layer and a hard shell layer; The hard core layer is mainly prepared from styrene, α-methylstyrene and water; The soft core layer is mainly prepared from alkyl acrylate and water, and the alkyl acrylate is selected from butyl acrylate and pentyl acrylate; The hard shell layer is a methacrylate polymer; Wherein, the mass ratio among the hard core layer, the soft core layer and the hard shell layer is (50~60): (30~40): (10~20).
[0006] In some specific embodiments, the hard core layer is mainly prepared from the following components in parts by weight: Styrene 27~33, α-Methylstyrene 23~27, Water 75~90; Based on the total weight of the styrene and the α-methylstyrene being 100%, the raw materials for preparing the hard core layer further include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Cross-linking agent 0.8%~1%.
[0007] In some embodiments, the soft core layer is mainly prepared from the following components in parts by weight: Alkyl acrylate 30~40, Water 45~60; Based on 100% by weight of the alkyl acrylate, the raw materials for preparing the soft core layer further include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Cross-linking agent 0.8%~1.2%.
[0008] In some embodiments, the hard shell layer is prepared from the following components in parts by weight: Methyl methacrylate 10~20, Water 15~30; Based on 100% by weight of the methyl methacrylate, the raw materials for preparing the hard shell layer further include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Crosslinking agent 0.3%~0.5%, Chain transfer agent 0.1%~0.2%.
[0009] In some specific embodiments, the chain transfer agent is dodecyl mercaptan.
[0010] In some embodiments, the emulsifier is selected from sodium alkyl sulfonate and / or sodium alkylbenzene sulfonate.
[0011] In some embodiments, the crosslinking agent is selected from one or more of allyl methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, or ethylene glycol dimethacrylate.
[0012] In some embodiments, the initiator is selected from a water-soluble redox composite initiator; wherein the oxidant in the water-soluble redox composite initiator is one or more of ammonium persulfate, potassium persulfate, diisopropylbenzene hydroperoxide or dibenzoyl peroxide; the reducing agent is sodium formaldehyde sulfoxylate, or a mixture of sodium formaldehyde sulfoxylate, ethylenediaminetetraacetic acid and ferrous sulfate.
[0013] In a second aspect, the present invention provides a method for preparing a transparent impact modifier for polyvinyl chloride, comprising: (1) Styrene, α-methylstyrene, emulsifier, crosslinking agent and water are placed in a reaction kettle, and after heating to the polymerization temperature, an initiator is added, and after the reaction is matured, a hard core layer emulsion is obtained; (2) adding alkyl acrylate, emulsifier, crosslinking agent and water to the reaction kettle, heating to the polymerization temperature, adding initiator, and reacting and maturing to obtain a hard core-soft core layer emulsion; (3) methyl methacrylate, emulsifier, crosslinking agent, chain transfer agent and water are continuously added into the reaction kettle, and after the temperature is raised to the polymerization temperature, an initiator is added, and after the reaction is matured, a hard core-soft core-hard shell layer emulsion is obtained; The prepared hard core-soft core-hard shell layer emulsion is flocculated and demulsified with a flocculant, and after washing and drying, a transparent impact modifier for polyvinyl chloride is obtained.
[0014] In some specific embodiments, in steps (1) and (2), the polymerization reaction is carried out at 60-65° C. for 3-4 hours; In step (3), the polymerization reaction is carried out at a temperature of 65-70°C for 2-3 hours; The flocculant is calcium chloride.
[0015] The technical solution provided by the present invention has the following beneficial effects: The transparent impact modifier for polyvinyl chloride provided by the invention has a three-layer structure of hard core-soft core-hard shell, and uses alkyl acrylate as the soft core layer to wrap the styrene monomer into the core, so that the modifier has good impact resistance while taking into account the yellowing resistance performance.
[0016] The modifier provided by the present invention also moderately crosslinks the hard shell layer, reduces the oligomers produced by incomplete depolymerization of the methyl methacrylate polymer, and reduces yellowing. At the same time, a chain transfer agent is added to the raw material components of the hard shell core layer, which improves the fluidity of the modifier in polyvinyl chloride and also improves the impact resistance of the product. DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.
[0019] The present invention provides a transparent impact modifier for polyvinyl chloride that is resistant to yellowing. The transparent impact modifier for polyvinyl chloride is a graft copolymer consisting of a hard core layer, a soft core layer and a hard shell layer. The hard core layer is mainly prepared from styrene, α-methylstyrene and water; The soft core layer is mainly prepared from alkyl acrylate and water, and the alkyl acrylate is selected from butyl acrylate and pentyl acrylate; The hard shell layer is a methacrylate polymer; Among them, the mass ratio between the hard core layer, the soft core layer and the hard shell layer is (50~60): (30~40): (10~20), for example, 55:35:15, 52:30:15.
[0020] In some specific embodiments, the hard core layer in the impact modifier provided by the present invention is mainly prepared from the following components in parts by weight: Styrene 27~33, α-Methylstyrene 23~27, Water 75~90; Based on the total weight of the above-mentioned styrene and α-methylstyrene being 100%, the raw materials for preparing the hard core layer also include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Cross-linking agent 0.8%~1%.
[0021] In the hard core layer of the transparent impact modifier for polyvinyl chloride provided by the present invention, alpha-methylstyrene is used to replace part of styrene, thereby improving the high temperature resistance of the product.
[0022] In some specific embodiments, the soft core layer in the impact modifier provided by the present invention is mainly prepared from the following components in parts by weight: Alkyl acrylate 30~40, Water 45~60; Based on 100% by weight of the alkyl acrylate, the raw materials for preparing the soft core layer also include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Cross-linking agent 0.8%~1.2%.
[0023] In some specific embodiments, the hard shell layer in the impact modifier provided by the present invention is prepared from the following components in parts by weight: Methyl methacrylate 10~20, Water 15~30; Based on 100% by weight of the methyl methacrylate, the raw materials for preparing the hard shell layer further include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Crosslinking agent 0.3%~0.5%, Chain transfer agent 0.1%~0.2%.
[0024] The transparent impact modifier for polyvinyl chloride provided by the present invention is also moderately cross-linked in the hard shell layer, thereby reducing the oligomers produced by incomplete depolymerization of methyl methacrylate and reducing the yellowing phenomenon of the product; at the same time, the added chain transfer agent can improve the fluidity of the modifier in polyvinyl chloride and improve the impact resistance of the product.
[0025] In some embodiments, the chain transfer agent is dodecyl mercaptan.
[0026] In some embodiments, the emulsifier used in the present invention is selected from sodium alkyl sulfonate and / or sodium alkylbenzene sulfonate. The emulsifier itself has a high decomposition temperature, high temperature resistance and strong emulsification ability, which greatly reduces the amount of emulsifier used. At the same time, the flocculation-drying production process can also reduce the emulsifier residue and reduce the yellowing problem caused by small molecules of the emulsifier.
[0027] In some embodiments, the crosslinking agent in the impact modifier provided by the present invention is selected from one or more of allyl methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate or ethylene glycol dimethacrylate.
[0028] In some embodiments, the initiator in the present invention is selected from a water-soluble redox composite initiator; wherein the oxidant in the water-soluble redox composite initiator is selected from one or more of ammonium persulfate, potassium persulfate, diisopropylbenzene hydroperoxide or dibenzoyl peroxide; the reducing agent is selected from sodium formaldehyde sulfoxylate, or a mixture of sodium formaldehyde sulfoxylate, ethylenediaminetetraacetic acid and ferrous sulfate.
[0029] The present invention also provides a method for preparing the transparent impact modifier for polyvinyl chloride, comprising: (1) Styrene, α-methylstyrene, emulsifier, crosslinking agent and water are placed in a reaction kettle, and after heating to the polymerization temperature, an initiator is added, and after the reaction is matured, a hard core layer emulsion is obtained; (2) adding alkyl acrylate, emulsifier, crosslinking agent and water to the reaction kettle, heating to the polymerization temperature, adding initiator, and reacting and maturing to obtain a hard core-soft core layer emulsion; (3) methyl methacrylate, emulsifier, crosslinking agent, chain transfer agent and water are continuously added into the reaction kettle, and after the temperature is raised to the polymerization temperature, an initiator is added, and after the reaction is matured, a hard core-soft core-hard shell layer emulsion is obtained; The prepared hard core-soft core-hard shell layer emulsion is flocculated and demulsified with a flocculant, and after washing and drying, a transparent impact modifier for polyvinyl chloride is obtained.
[0030] In some embodiments, in steps (1) and (2), the polymerization reaction is carried out at 60-65° C. for 3-4 hours; In step (3), the polymerization reaction is carried out at a temperature of 65-70°C for 2-3 hours; In some preferred embodiments, the flocculant is selected from calcium chloride.
[0031] The present invention is further described below by means of specific examples, but it should not be understood that the present invention is limited thereto.
[0032] Where specific experimental steps or conditions are not specified in the examples, the experiments can be carried out according to the corresponding conventional experimental steps or conditions in the art. The reagents used without specifying the manufacturer are all conventional reagents available in the art.
[0033] Sources of raw materials for the following examples: Styrene: Lihua Yilijin Refining and Chemical Co., Ltd., industrial grade; α-Methylstyrene: Wuhan Jiyesheng Chemical Co., Ltd., industrial pure; Butyl acrylate: Wanhua Chemical Group Co., Ltd., industrial grade; Amyl acrylate: Hubei Xinhongli Chemical Co., Ltd., industrial pure; Potassium persulfate: Yatai Electrochemical Co., Ltd., industrial grade; Sodium alkyl sulfonate: Henan Lichi Fine Chemical Co., Ltd., industrial grade; Sodium alkylbenzene sulfonate: Guangzhou Fufei Chemical Technology Co., Ltd., industrial grade.
[0034] Example 1 (1) 81 kg of styrene, 81 kg of α-methylstyrene, 0.81 kg of sodium alkyl sulfonate, 1.62 kg of allyl methacrylate, and 243 kg of water were added into a 1-ton reactor, and the temperature was raised to a polymerization temperature of 65°C. Then, 0.0648 kg of potassium persulfate and 0.0648 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 3 hours and then matured to obtain a hard core layer emulsion; (2) 108 kg of butyl acrylate, 0.54 kg of sodium alkyl sulfonate, 162 kg of water, and 1.08 kg of allyl methacrylate were added to the reactor, and after the temperature was raised to the polymerization temperature of 65°C, 0.0432 kg of potassium persulfate and 0.0432 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 3 hours and then matured to obtain a hard core-soft core layer emulsion; (3) 30 kg of methyl methacrylate, 0.15 kg of sodium alkyl sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 70°C, and then 0.012 kg of potassium persulfate and 0.012 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 2 h and then matured to obtain a hard core-soft core-hard shell emulsion.
[0035] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter and then entered into a drying bed for drying at 60° C. to finally obtain a powder product.
[0036] Example 2 (1) 81 kg of styrene, 69 kg of α-methylstyrene, 0.75 kg of sodium alkyl sulfonate, 1.5 kg of 1,6-hexanediol diacrylate, and 225 kg of water were added into a 1-ton reactor, the temperature was raised to a polymerization temperature of 65°C, 0.06 kg of potassium persulfate and 0.06 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core layer emulsion; (2) 90 kg of amyl acrylate, 0.45 kg of sodium alkyl sulfonate, 135 kg of water, and 0.9 kg of 1,6-hexanediol diacrylate were added to the reactor, and after the temperature was raised to the polymerization temperature of 65°C, 0.036 kg of potassium persulfate and 0.036 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core-soft core layer emulsion; (3) 60 kg of methyl methacrylate, 0.3 kg of sodium alkyl sulfonate, 90 kg of water, 0.3 kg of ethylene glycol dimethacrylate and 0.06 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 70°C, and then 0.024 kg of potassium persulfate and 0.024 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 3 h and then matured to obtain a hard core-soft core-hard shell layer emulsion.
[0037] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter and then entered into a drying bed for drying at 60° C. to finally obtain a powder product.
[0038] Example 3 (1) 93 kg of styrene, 69 kg of α-methylstyrene, 0.81 kg of sodium alkylbenzene sulfonate, 1.62 kg of allyl methacrylate, and 243 kg of water were added into a 1-ton reactor, and the temperature was raised to a polymerization temperature of 60°C. Then, 0.0648 kg of potassium persulfate and 0.0648 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 3 hours and then matured to obtain a hard core layer emulsion; (2) 108 kg of butyl acrylate, 0.54 kg of sodium alkylbenzene sulfonate, 162 kg of water, and 1.08 kg of allyl methacrylate were added to the reactor, and after the temperature was raised to the polymerization temperature of 60°C, 0.0432 kg of potassium persulfate and 0.0432 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 3 hours and then matured to obtain a hard core-soft core layer emulsion; (3) 30 kg of methyl methacrylate, 0.15 kg of sodium alkylbenzene sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 65°C, and then 0.012 kg of potassium persulfate and 0.012 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 2 h and then matured to obtain a hard core-soft core-hard shell emulsion.
[0039] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter and then entered into a drying bed for drying at 60° C. to finally obtain a powder product.
[0040] Example 4 (1) 87 kg of styrene, 75 kg of α-methylstyrene, 1.134 kg of sodium alkyl sulfonate, 1.62 kg of allyl methacrylate, and 243 kg of water were added into a 1-ton reactor, the temperature was raised to a polymerization temperature of 60°C, 0.0324 kg of ammonium persulfate and 0.0324 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 3 hours and then matured to obtain a hard core layer emulsion; (2) 108 kg of butyl acrylate, 0.756 kg of sodium alkyl sulfonate, 162 kg of water, and 1.08 kg of allyl methacrylate were added to the reactor, and after the temperature was raised to the polymerization temperature of 60°C, 0.0216 kg of ammonium persulfate and 0.0216 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 3 hours and then matured to obtain a hard core-soft core layer emulsion; (3) 30 kg of methyl methacrylate, 0.21 kg of sodium alkyl sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 65°C, and then 0.006 kg of ammonium persulfate and 0.006 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 2 h and then matured to obtain a hard core-soft core-hard shell emulsion.
[0041] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter and then entered into a drying bed for drying at 60° C. to finally obtain a powder product.
[0042] Example 5 (1) 99 kg of styrene, 81 kg of α-methylstyrene, 0.9 kg of sodium alkyl sulfonate, 1.8 kg of ethylene glycol dimethacrylate, and 270 kg of water were added into a 1-ton reactor, the temperature was raised to a polymerization temperature of 60°C, 0.072 kg of potassium persulfate and 0.072 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 3 hours and then matured to obtain a hard core layer emulsion; (2) 90 kg of butyl acrylate, 0.45 kg of sodium alkyl sulfonate, 135 kg of water, and 0.9 kg of ethylene glycol dimethacrylate were added to the reactor, and the temperature was raised to the polymerization temperature of 60°C. Then, 0.036 kg of potassium persulfate and 0.036 kg of sodium formaldehyde sulfoxylate were added, and the reaction was continued for 3 hours and then matured to obtain a hard core-soft core layer emulsion; (3) 30 kg of methyl methacrylate, 0.15 kg of sodium alkyl sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added into the reactor. The temperature was raised to the polymerization temperature of 65°C, and then 0.012 kg of potassium persulfate and 0.012 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 2 h and then matured to obtain a hard core-soft core-hard shell emulsion.
[0043] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter, and then placed in a drying bed for drying at 60° C. to finally obtain a powder product.
[0044] Example 6 (1) 81 kg of styrene, 69 kg of α-methylstyrene, 0.75 kg of sodium alkyl sulfonate, 1.5 kg of ethylene glycol dimethacrylate, and 225 kg of water were added into a 1-ton reactor, and the temperature was raised to a polymerization temperature of 63°C, and then 0.06 kg of a mixture of potassium persulfate and sodium formaldehyde sulfoxylate (the mass ratio of sodium formaldehyde sulfoxylate to ethylenediaminetetraacetic acid and ferrous sulfate was 2:0.01:0.01) was added, and the reaction was continued for 3.5 hours and then matured to obtain a hard core layer emulsion; (2) 120 kg of amyl acrylate, 0.6 kg of sodium alkyl sulfonate, 180 kg of water, and 1.2 kg of ethylene glycol dimethacrylate were added to the reactor, and the temperature was raised to the polymerization temperature of 63°C, and then 0.048 kg of potassium persulfate and 0.048 kg of a mixture of sodium formaldehyde sulfoxylate (the mass ratio of sodium formaldehyde sulfoxylate to ethylenediaminetetraacetic acid and ferrous sulfate was 2:0.01:0.01) were added, and the mixture was reacted for 3.5 hours and aged to obtain a hard core-soft core layer emulsion; (3) 30 kg of methyl methacrylate, 0.15 kg of sodium alkyl sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 68°C, and then 0.012 kg of a mixture of potassium persulfate and sodium formaldehyde sulfoxylate (the mass ratio of sodium formaldehyde sulfoxylate to ethylenediaminetetraacetic acid and ferrous sulfate was 2:0.01:0.01) was added. The mixture was reacted for 2.5 h and then aged to obtain a hard core-soft core-hard shell emulsion.
[0045] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter, and then placed in a drying bed for drying at 60° C. to finally obtain a powder product.
[0046] Example 7 (1) 81 kg of styrene, 81 kg of α-methylstyrene, 0.81 kg of sodium alkyl sulfonate, 1.296 kg of ethylene glycol dimethacrylate, and 243 kg of water were added into a 1-ton reactor, the temperature was raised to a polymerization temperature of 65°C, 0.0648 kg of diisopropylbenzene hydroperoxide and 0.0648 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core layer emulsion; (2) 108 kg of butyl acrylate, 0.54 kg of sodium alkyl sulfonate, 162 kg of water, and 0.864 kg of ethylene glycol dimethacrylate were added to the reactor, and the temperature was raised to the polymerization temperature of 65°C. Then, 0.0432 kg of diisopropylbenzene hydroperoxide and 0.0432 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 4 hours and then matured to obtain a hard core-soft core layer emulsion. (3) 30 kg of methyl methacrylate, 0.15 kg of sodium alkyl sulfonate, 45 kg of water, 0.09 kg of ethylene glycol dimethacrylate and 0.06 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 70°C, and then 0.012 kg of diisopropylbenzene hydroperoxide and 0.012 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 3 h and then matured to obtain a hard core-soft core-hard shell emulsion.
[0047] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter and then entered into a drying bed for drying at 60° C. to finally obtain a powder product.
[0048] Comparative Example 1 (1) 87 kg of styrene, 75 kg of α-methylstyrene, 108 kg of butyl acrylate, 1.35 kg of sodium alkyl sulfonate, 2.70 kg of allyl methacrylate, and 405 kg of water were added into a 1-ton reactor, the temperature was raised to a polymerization temperature of 60°C, 0.108 kg of potassium persulfate and 0.108 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core layer emulsion; (2) 30 kg of methyl methacrylate, 0.15 kg of sodium alkyl sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 70°C, and then 0.012 kg of potassium persulfate and 0.012 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 3 hours and then the core-shell emulsion was obtained.
[0049] The prepared emulsion was placed in a drying tower and dried at 220° C. to obtain a powdery product.
[0050] Comparative Example 2 (1) 87 kg of styrene, 75 kg of α-methylstyrene, 0.81 kg of sodium alkyl sulfonate, 1.62 kg of allyl methacrylate, and 243 kg of water were added into a 1-ton reactor, and the temperature was raised to a polymerization temperature of 65°C. Then, 0.0648 kg of potassium persulfate and 0.0648 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core layer emulsion; (2) 108 kg of methyl acrylate, 0.54 kg of sodium alkyl sulfonate, 162 kg of water, and 1.08 kg of allyl methacrylate were added to the reactor, and after the temperature was raised to the polymerization temperature of 65°C, 0.0432 kg of potassium persulfate and 0.0432 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core-soft core layer emulsion; (3) 30 kg of methyl methacrylate, 0.15 kg of sodium alkyl sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 70°C, and then 0.012 kg of potassium persulfate and 0.012 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 3 h and then matured to obtain a hard core-soft core-hard shell emulsion.
[0051] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter, and then entered into a drying bed for drying at 60° C. to finally obtain a powder product.
[0052] Comparative Example 3 (1) 162 kg of styrene, 0.81 kg of sodium alkyl sulfonate, 1.62 kg of allyl methacrylate, and 243 kg of water were added to a 1-ton reactor, and the temperature was raised to a polymerization temperature of 65°C. Then, 0.0648 kg of potassium persulfate and 0.0648 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core layer emulsion; (2) 108 kg of butyl acrylate, 0.54 kg of sodium alkyl sulfonate, 162 kg of water, and 1.08 kg of allyl methacrylate were added to the reactor, and after the temperature was raised to the polymerization temperature of 65°C, 0.0432 kg of potassium persulfate and 0.0432 kg of sodium formaldehyde sulfoxylate were added, and the reaction was carried out for 4 hours and then matured to obtain a hard core-soft core layer emulsion; (3) 30 kg of methyl methacrylate, 0.15 kg of sodium alkyl sulfonate, 45 kg of water, 0.15 kg of ethylene glycol dimethacrylate and 0.03 kg of dodecyl mercaptan were added to the reactor. The temperature was raised to the polymerization temperature of 70°C, and then 0.012 kg of potassium persulfate and 0.012 kg of sodium formaldehyde sulfoxylate were added. The reaction was continued for 3 h and then matured to obtain a hard core-soft core-hard shell emulsion.
[0053] The hard core-soft core-hard shell layer emulsion prepared above was flocculated and demulsified by calcium chloride, dried by a filter, and then placed in a drying bed for drying at 60° C. to finally obtain a powder product.
[0054] The modifier obtained in the above example is added into the preparation process of polyvinyl chloride according to the following ratio. Specifically, the raw materials in Table 1 are mixed in a high-speed mixer at 85°C, and then discharged after cooling to 44°C; then, the mixed reaction raw materials are passed through a 40-mesh sieve and mixed in a double-roll mill. The mixing parameters are shown in Table 2 below: Table 1
[0055] Table 2
[0056] According to T / CCASC 3002-2023 "Double-roll milling method for dynamic thermal stability test of polyvinyl chloride", the polyvinyl chloride sheets in the double-roll mill were sliced and sampled at different times, and the yellow index of the polyvinyl chloride slices was tested according to GB / T 39822-2021 "Determination of the yellow index of plastics and its change value". The test results are shown in Table 3: Table 3
[0057] The modifiers obtained in the above examples were mixed according to the proportions in Table 1 above, and then sieved through a 40-mesh sieve and mixed on a double-roll mill (refer to Table 2 above for parameters) and vulcanized on a flat vulcanizer (refer to Table 4 below for parameters) to form a plate.
[0058] Table 4
[0059] According to GB-T 1043.1-2008 "Determination of simply supported beam impact properties of plastics Part 1 Non-instrumented impact test", sample preparation and simply supported beam impact strength (A-notch) test were carried out. The test results are shown in Table 5: Table 5
[0060] From the above test results, the polyvinyl chloride material prepared by using the impact modifier of the hard core-soft core-hard shell three-layer structure provided by the present invention has a lower yellowing resistance index and a higher simply supported beam impact strength.
Claims
1. A transparent impact modifier for polyvinyl chloride that is resistant to yellowing, characterized in that: The transparent impact modifier for polyvinyl chloride is a graft copolymer consisting of a hard core layer, a soft core layer and a hard shell layer; The hard core layer is mainly prepared from styrene, α-methylstyrene and water; The soft core layer is mainly prepared from alkyl acrylate and water, and the alkyl acrylate is selected from butyl acrylate and pentyl acrylate; The hard shell layer is a methacrylate polymer; Wherein, the mass ratio among the hard core layer, the soft core layer and the hard shell layer is (50~60): (30~40): (10~20).
2. The transparent impact modifier for polyvinyl chloride according to claim 1, characterized in that: The hard core layer is mainly prepared from the following components in parts by weight: Styrene 27~33, α-Methylstyrene 23~27, Water 75~90; Based on the total weight of the styrene and the α-methylstyrene being 100%, the raw materials for preparing the hard core layer further include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Cross-linking agent 0.8%~1%.
3. The transparent impact modifier for polyvinyl chloride according to claim 2, characterized in that: The soft core layer is mainly prepared from the following components in parts by weight: Alkyl acrylate 30~40, Water 45~60; Based on 100% by weight of the alkyl acrylate, the raw materials for preparing the soft core layer further include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Cross-linking agent 0.8%~1.2%.
4. The transparent impact modifier for polyvinyl chloride according to claim 3, characterized in that: The hard shell layer is prepared from the following components in parts by weight: Methyl methacrylate 10~20, Water 15~30; Based on 100% by weight of the methyl methacrylate, the raw materials for preparing the hard shell layer further include: Emulsifier 0.5%~0.7%, Initiator 0.04%~0.08%, Crosslinking agent 0.3%~0.5%, Chain transfer agent 0.1%~0.2%.
5. The transparent impact modifier for polyvinyl chloride according to claim 4, characterized in that: The chain transfer agent is selected from dodecyl mercaptan.
6. The transparent impact modifier for polyvinyl chloride according to any one of claims 2 to 5, characterized in that: The emulsifier is selected from sodium alkyl sulfonate and / or sodium alkylbenzene sulfonate.
7. The transparent impact modifier for polyvinyl chloride according to claim 6, characterized in that: The crosslinking agent is selected from one or more of allyl methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate or ethylene glycol dimethacrylate.
8. The transparent impact modifier for polyvinyl chloride according to claim 7, characterized in that: The initiator is selected from water-soluble redox composite initiators; The oxidant in the water-soluble redox composite initiator is one or more of ammonium persulfate, potassium persulfate, diisopropylbenzene hydroperoxide or dibenzoyl peroxide; the reducing agent is sodium formaldehyde sulfoxylate, or a mixture of sodium formaldehyde sulfoxylate, ethylenediaminetetraacetic acid and ferrous sulfate.
9. A method for preparing the transparent impact modifier for polyvinyl chloride according to any one of claims 1 to 8, characterized in that: include: (1) Styrene, α-methylstyrene, emulsifier, crosslinking agent and water are placed in a reaction kettle, and after heating to the polymerization temperature, an initiator is added, and after the reaction is matured, a hard core layer emulsion is obtained; (2) adding alkyl acrylate, emulsifier, crosslinking agent and water to the reaction kettle, heating to the polymerization temperature, adding initiator, and reacting and maturing to obtain a hard core-soft core layer emulsion; (3) methyl methacrylate, emulsifier, crosslinking agent, chain transfer agent and water are continuously added into the reaction kettle, and after the temperature is raised to the polymerization temperature, an initiator is added, and after the reaction is matured, a hard core-soft core-hard shell layer emulsion is obtained; The prepared hard core-soft core-hard shell layer emulsion is flocculated and demulsified with a flocculant, and after washing and drying, a transparent impact modifier for polyvinyl chloride is obtained.
10. The preparation method according to claim 9, characterized in that: In steps (1) and (2), the polymerization reaction is carried out at 60-65° C. for 3-4 hours; In step (3), the polymerization reaction is carried out at a temperature of 65-70°C for 2-3 hours; The flocculant is calcium chloride.
Citation Information
Patent Citations
Transparent acrylic ester impact-resisting modifier for PVC
CN101190992A
Thermoplastic composition and articles having high impact strength and good appearance
CN101341214A
Transparent polyvinyl chloride toughening modifier with three-layer nuclear shell structure and preparation method thereof
CN101544731A
Polyvinyl chloride mixture with impact resistance and excellent processability
CN101891866A
High-rigidity transparent rigid polyvinyl chloride granule and preparation method thereof
CN119684727A
Cited By
Nanometer enhanced impact modifier for polyvinyl chloride and preparation method of nanometer enhanced impact modifier
CN120757947A
Nanometer reinforced impact modifier for polyvinyl chloride and its preparation method
CN120757947B
Multilayer composite cross-linked polymer as well as preparation method and application thereof
CN122381262A